Sharia Based Economic and Business Strategies in Bima Craft Army at Stit Sunan Giri Bima - Yusuf, Yusuf; Rosdiyanti, Evi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study discusses the implementation of Sharia-based economic and business strategies at Laskar Bima Craft (LBC) at STIT Sunan Giri Bima. LBC implements Sharia principles such as profit-sharing systems, transparency, and avoiding prohibited practices such as usury and gharar in its business operations. This study uses a descriptive qualitative approach with a case study design to deeply understand the implementation of Sharia strategies by LBC. The results of the study indicate that LBC applies the principle of honesty in transactions and builds trust with customers through quality products. However, LBC faces challenges in the form of a low public understanding of Sharia economics and limited access to Sharia financing. To overcome these obstacles, LBC seeks to improve Sharia education, diversify financing sources, and continue to innovate in product development. This study suggests that LBC strengthen the socialisation of Sharia concepts to the community and develop member capacity to ensure competitiveness in the local market.